2010
DOI: 10.1175/2009jhm1194.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing High-Latitude Winter Precipitation from Global Precipitation Analyses Using GRACE

Abstract: This study compares cold-season, high-latitude precipitation estimates from two global, merged satellitegauge precipitation analyses-Global Precipitation Climatology Project (GPCP) and Climate Prediction Center Merged Analysis of Precipitation (CMAP)-to total water storage anomalies produced from the Gravity Recovery and Climate Experiment (GRACE). In general, spatial patterns and interannual variability are highly correlated between the datasets, although significant differences are also observed. Differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 25 publications
(39 reference statements)
4
23
0
Order By: Relevance
“…Similar, overestimation of precipitation undercatch correction in GPCP has been reported by Swenson (2010). Taking into account the mismatch in temporal and spatial domains, as well as the experimental definitions, reducing GPCP snowfall in our study by 33 % is roughly consistent with both studies.…”
Section: Model Optimizationsupporting
confidence: 91%
“…Similar, overestimation of precipitation undercatch correction in GPCP has been reported by Swenson (2010). Taking into account the mismatch in temporal and spatial domains, as well as the experimental definitions, reducing GPCP snowfall in our study by 33 % is roughly consistent with both studies.…”
Section: Model Optimizationsupporting
confidence: 91%
“…This reduction agrees with Behrangi et al (2016), who found GPCP to overestimate snowfall over Eurasian high latitudes. Similar, overestimation of precipitation undercatch correction in GPCP has also been reported by Swenson (2010). Therefore, psf allows to reduce inconsistencies between the precipitation forcing and the water storages as given by GlobSnow SWE and GRACE TWS.…”
Section: Model Optimizationsupporting
confidence: 72%
“…The changes in bias and RMSE (and anomaly R) between MERRA and MERRA-Land are primarily due to the GPCP-based precipitation corrections and are not related to the snow parameter changes (not shown). The snow depth bias may be higher in MERRA-Land because the precipitation gauge undercatch may have been overcorrected in the GPCP precipitation in northern high latitudes (Swenson 2010). A potential bias in the WMO snow depth observations, however, offers another explanation.…”
Section: Snowmentioning
confidence: 99%